Analisis dan Perancangan Sistem Informasi Data Perikanan Di Pelabuhan Perikanan Nusantara Karangantu - Fatullah, Rizki; Solihati, Tifani Intan; Maulana, Fikri Sulaiman; Hidayanti, Nur (Teknik Informatika Fakultas Ilmu Komputer, 2024)
The data is recapitulated into a report to the institution. PPN Karangantu is an institution tasked with managing data on fisheries caught by fishermen. As an employee in the fisheries catch data management section, he is tasked with managing fishermen's catch data, starting from fishing vessel data, number of catches, types of catches, and recap reports. In this activity, the Enumerator had problems with the capture fisheries data management process. Based on the existing problems, employees to carry out rework so that the time required is longer. this paper uses the Waterfall method as a system development method, system modeling uses Unified Modeling Language (UML), as well as a system display design that provides a general description of the system being created. The result of this research is that the Fisheries Data Information System can assist the Karangantu PPN agency in reporting recap activities and managing fishing data.